Characterization of silkworm larvae growth and properties of silk fibres after direct feeding of copper or silver nanoparticles. (5th September 2017) - Cheng, Lan; Huang, Huiming; Chen, Shaoyong; Wang, Wenlu; Dai, Fangyin; Zhao, Hongping
Abstract: In this study, we raised silkworm larvae from the fifth instar with a modified diet of copper or silver nanoparticles (NPs) combined with mulberry leaves. Silkworm larvae growth was characterized according to larvae weight, survival rate, cocooning and silk glands microstructures. Cu or Ag element distributions in their tissues were examined with inductively couple plasma mass spectroscopy. The properties of silkworm silks were investigated with Fourier transform infrared (FTIR) and amino acid analyses, thermogravimetric and quasi-static tensile tests. Our results depicted a primary concentration distribution map of Cu or Ag element in silkworm larva tissues by the modified diet, and Cu or Ag NPs had slightly negative influences on the growth of the silkworm larvae. Results from FTIR spectra and amino acid analyses showed that the Cu or Ag NPs slightly inhibited the β -sheet conformation transition and promoted the crystallization of silk protein. Furthermore, copper or silver NPs obviously enhanced the thermal stability and mechanical properties of silkworm silk with a coupling competitive mechanism. This study expands our ability to obtain distinctive reinforced silkworm silks in a green and effective way and to gain an elementary comprehension of nano-bio interactions between a model organism, Bombyx mori silkworm, and metallic nanoparticles. Graphical abstract: Highlights: Silk fibres with reinforced thermal and mechanical properties were obtained after feeding copper or sliver nanoparticles. Copper or silver element concentration distributions in silkworm larvae tissues and silk fibres were first acquired. Metal nanoparticles slightly inhibited the β -sheet conformation transition and promoted crystallization of silk protein. This study expands our ability to obtain distinctive reinforced silkworm silks with a green and effective way.